Une succession de référence pour le Toarcien Moyen et Supérieur: les "Margas calcárias de São Gião" dans les environs de Cantanhede (sous-bassin nord lusitanien, Portugal)* - Elmi, S. (2011)
The geological sections studied at the São Gião sector (Cantanhede region) have allowed the establishment of a clear succession of ammonite associations during the Middle and Upper Toarcian (“Margas calcárias de São Gião” and “Calcários margosos de Póvoa da Lomba” Formations). The fossil collections were gathered over the last 40 years and, in spite of the apparent facies monotony, come from a thick and fossiliferous marly-limestone unit. The ammonite succession allows the establishment and/or verification of a certain number of biostratigraphical elements, of which are worthy of mention: – the tethyan character of the fauna from the Gradata to the Meneghinii Zones; this differentiation starts with the occurrence of Collina, Crassiceras and Furloceras of the Gradata Zone; – the succession of Osperleioceras, with the connection between the “caussenardes”(O. reynesi, O. authelini) forms and those from Algeria (O. nadorense, O. matteii), which is placed at the beginning of the Aalensis Zone; – the succession of Hammatoceratinae: H. roubanense (Gradata Z.), H. bonarellii (Bonarellii Z.), H. speciosum (Speciosum Sub-zone), followed by Crestaites meneghinii (Reynesi Sub-zone and Meneghinii Z.); Pseudaptetoceras appear next (Aalensis Zone). The dynamic evolution of the sector is characterized by the persistence of marly sedimentation during the Meneghinii Zone, in probable relation to the paleostructural play of the Arunca-Montemor meridian axis.